PENGARUH PNPM-MKP TERHADAP PENINGKATAN PENDAPATAN KELOMPOK TANI IKAN DESA PERING KECAMATAN BLAHBATUH KABUPATEN GIANYAR - Murdini, Ida Ayu Ketut; Agung, A.A. Putu; Martiningsih, Ni GAG. Eka (Alam Lestari, 2012)
The National Community Empowerment Program (NCEP) is a poverty reduction program that targets the areas of Maritime Affairs and Fisheries both coastal region and outside the coastal marine and fisheries activities in the field. The purpose of this study was to determine the effect of The National Community Empowerment Program on the economy of the fish farmers. This research was conducted in the Pering village of Sub district of Blahbatuh, Gianyar regency. Data collected by direct observation in the field and also used a questionnaire to all fish farmers group member who totaled 67 people. Descriptive data were analyzed using the statistical program R-GUI. Data analysis of fish farmers income differences before and after the PNPM program M-KP computed X2.This study proves that before NCEP program implemented are as follows: (a). The proportion of fish farmers in the Pering village that maintains shrimp commodities dominate in the maintenance of commodities, namely 53.7%, while the smallest proportion was found that the carp maintains commodities, namely 7.5%. Other types of commodities that are maintained by fish farmers in the Pering village pomfret, tilapia, carp and catfish. (b). Average frequency of fish farmers harvest in a year that maintains a commodity type of shrimp is 1.58 times, and (c). Average income of fish farmer is Rp. 2,930,597.02;Meanwhile, after execution of the NCEP, it can be proved the following: (a). The proportion of fish farmers who maintain the type of commodity augmentation catfish dominate in the maintenance of commodities (68.66%) while the smallest proportion was found that the fish farmers who maintain the type of commodity augmentation carp (7.46%). Another type of commodity is maintained catfish hatchery and rearing tilapia. (b). Average frequency of fish farmers harvest in a year that maintains a commodity type of catfish is 2.63 times magnification, and (c). Average income of fish farmers is Rp. 3,539,552.24. This study also shows that the income of fish farmers in the Pering village after the implementation of the NCEP greater than before. (Î± <0.05).